Pengetahuan, Usia Ibu Hamil Lanjut, dan Risiko Komplikasi Kehamilan di Wilayah Kerja Puskesmas Bonebobakal - Kartini S; Eka Fadillah Bagenda (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Pregnancy complications remain a major health problem contributing to high maternal morbidity and mortality rates in Indonesia. Factors influencing the occurrence of pregnancy complications include the level of maternal knowledge and advanced maternal age. Advanced age increases the risk of pregnancy disorders due to decreased reproductive function, while low knowledge limits a mother’s ability to recognize danger signs and take appropriate preventive measures. This study aimed to determine the relationship between knowledge level and advanced maternal age and the occurrence of pregnancy complications in the working area of Bonebobakal Public Health Center, Banggai Regency. This study employed a quantitative analytic design with a cross-sectional approach involving 41 pregnant women selected through total sampling. Data were collected using questionnaires and interviews and analyzed using the Chi-Square test. The results showed a significant relationship between maternal knowledge level and maternal age with the occurrence of pregnancy complications. Health education and regular pregnancy monitoring are necessary to reduce the risk of complications and improve maternal and fetal safety..